Line characteristics and performance in giant slalom - Spörri, J.; Kröll, J.; Schiefermüller, C.; Müller, E. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: While in the past the fastest turn was thought to be a purely carved turn with the smallest energy dissipation possible, nowadays tighter arcs and drifted turns can be observed in top level ski racing. These kinds of line characteristics result in higher energy dissipation during a direction change and higher velocity gains during the transition. Recent studies in slalom (Reid et al. 2007, Supej et al. 2010) mainly investigated the influence of different parameters on energy dissipation as a predictor of performance. In Giant Slalom (GS) however the distance between gates is greater and the potential for velocity gains during the transition is higher. The aim of this study was to show how a Top World Class Athlete intuitively deals with the individual and situational compromise of maximizing speed and minimizing energy losses on a typical GS section with conditions similar to world cup.